How is Ulster’s History Represented in Northern Ireland’s Museums? The Cases of the Ulster Folk Museum and the Ulster Museum - Karine BIGAND (E-REA)
The ongoing over-sensitive relation between memory and politics in Northern Ireland has had an impact on the representation of history in museums, in particular the representation of the recent past and the “Troubles”. This is particularly true of the state museums that have been noted for, at best, their general embarrassment in the representation of history, at worst, their avoidance of it. This paper focuses on the representation of Ulster’s history in the Ulster Folk and Transport Museum in Cultra and in the Ulster Museum in Belfast. It addresses the ideological outlook behind the fluctuating presentations of history and reflects on the role of museums as mediator between communities in a post-conflict, yet still divided Northern Irish society.